Options of dyslipidemia treatment at non-alcoholic fatty liver disease - M. V. Mayevskaya; M. A. Morozova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of review. To consider different treatment options for dyslipidemia in non-alcoholic fatty liver disease (NAFLD). Summary. NAFLD occurs in 20-30% of adult population. In the Russian Federation its rate is estimated as high as 37,1%. In the most of NAFLD cases severe disorder of lipid metabolism takes place. In large clinical trials it was demonstrated that the dyslipidemia significantly increases cardiovascular risks and worsens life expectancy in these patients. In the present overview treatment options of several therapeutic agents for dyslipidemia treatment at NAFLD are discussed: phenofibrate, omega-3 polyunsaturated fatty acids (omega-3-PUFAs) and S-adenosylmethionine (SAM). Results of numerous experiments and several clinical trials form the basis for phenofibrate administration for NAFLD patients. In animal experiments the positive role of phenofibrate as PPARα agonist was demonstrated (Peroxisome proliferator activated receptor alpha) for NAFLD prevention and treatment. Results of several studies published at the moment demonstrate that at NAFLD lipid metabolism markers, and serum transaminase levels normalize, sensitivity to insulin increases, the liver histology pattern improves at phenofibrate treatment. Specification of efficacy and safety of application of the drug requires more large-scale clinical studies. Omega-3-PUFAs is one more option in the lipid metabolism disorders treatment in this group of patients. These substances play important role in lipid metabolism regulating expression of the genes (including PPARα) involved in lipid and glucose metabolism. Available clinical trials demonstrate high therapeutical effect of these agents at NAFLD. In the review results of the experimental studies investigating the role of SAM in NAFLD pathogenesis and disorders of lipid metabolism is presented. Conclusion. Now data on a pathogenesis of lipid metabolism disorders at NAFLD are accumulated. The bulk of experimental data and series of clinical trials allow to assume positive affect of such drugs as phenofibrate, omega-3-PUFA and SAMe for treatment of dyslipidemia. Further high-grade studies in this area is necessary.